Validity of parental recall of children's fracture: implications for investigation of childhood osteoporosis. Issue 2 (February 2016) - Moon, R.; Lim, A.; Farmer, M.; Segaran, A.; Clarke, N.; Harvey, N.; Cooper, C.; Davies, J.
Abstract Summary Fracture history is an important component of osteoporosis diagnosis in children. One in six parentally reported lifetime fractures in children were not confirmed on review of radiographs. Care should be taken to avoid unnecessary investigations for possible osteoporosis due to parental over-reporting of soft tissue injuries as fractures. Introduction The diagnosis of osteoporosis in children requires either a vertebral compression fracture, or a significant fracture history (defined as ≥2 long bone fractures <10 years or ≥3 long bone fractures <19 years, excluding high impact fractures) and low bone mineral density. As children with frequent fractures might benefit from further evaluation, we determined whether parental reports of lifetime fracture were accurate compared to radiological reports and if they appropriately selected children for further consideration of osteoporosis. Methods Parents of children (<18 years) with a musculoskeletal injury completed a questionnaire on their child's fracture history, including age, site and mechanism of previous fracture(s). Radiological reports were reviewed to confirm the fracture. Results Six hundred sixty parents completed the questionnaire and reported 276 previous fractures in 207 children. An injury treated at our hospital was recorded in 214 of the 276 parentally reported fractures. Thirty-four of 214 (16 %) were not a confirmed fracture. An injury was recorded for all parentally reported fractures in 150 children, but for 21 % children, there were inaccurate details (no evidence of fracture, incorrect site or forgotten fractures) on parent report. Eighteen of 150 children had a significant fracture history on parental report alone, but following review of radiology reports, 2 of 18 (11 %) did not have clinically significant fracture histories. Conclusions Approximately one in six fractures reported by parents to have occurred in their child's lifetime had not resulted in a fracture. One in nine children with a significant fracture history could have been investigated unnecessarily.